Effect of feeding bypass protein on milk production performance crossbred cow - CHANDRASEKHARAIAH, M; SAMPATH, K T; PRAVEEN, U S (The Indian Journal of Animal Sciences, 2011)
On-farm lactation trial of 4 months duration was conducted in Anagalpura and Menesi village of Doddaballapura taluk, Bangalore district in Kamataka state to study the effect of feeding bypass protein (UDP) on the milk production performance of crossbred cows. Crossbred cows (24) yielding 8 to 10 Htres of milk/day were divided into 2 comparable groups (control and experimental) of 12 each based on lactation number, milk yield and days after calving. Cows in control group were fed a concentrate mixture (CMC) which contained 37% of CP as UDP (bypass protein), while those in experimental group were fed a concentrate mixture (CME) containing 50% CP as UDP. The animals in both the groups were fed ad lib. local mixed grass as the major source of roughage. The average milk yield per day in experimental group was significantly higher than those in control group. The milk fat, SNF and total solids were significantly higher in experimental animals than in control group animals. The milk yield was increased by 1.07 litres, feed cost was reduced by Rs 2.20 and the overall income of the farmers was increased by Rs 12.40/cQw/day in experimental group. The study indicated that feeding of bypass protein increased quantity and quality of milk in cows producing 8-10 litres milk/day on local mixed grass based diets.Â